EU Member States' capabilities in conflict prevention and peacebuilding: personnel and technology. Issue 2 (27th May 2018) - Pirozzi, Nicoletta; Venturi, B.; Marrone, A.
ABSTRACT: This article provides an overview of Member States' key capabilities – namely personnel and technology – in light of main EU goals in conflict prevention and peacebuilding, revealing a heterogeneous landscape. While acknowledging that the EU owns some of these capabilities, the article is primarily intended to highlight the assets and manpower available at the national level, with a view to understanding how these capabilities might better support and strengthen the EU's role in conflict prevention and peacebuilding. Relevant data collected through four case studies – France, Germany, Italy, and Sweden – is used to understand if currently available capabilities are adequate to match EU objectives. In the context of the EU's integrated approach, key policy recommendations are put forward to better integrate national civilian and dual-use capabilities for the creation of a functioning EU early warning/situational awareness system, in order to anticipate, describe and diagnose conflicts, as well as to implement effective responses.